(untitled) (Advancements in Homeopathic Research, 2022)
Chronic bronchitis is one disease, which is difficult to treat with conventional medicines as these could give the palliation for a period of time. To combat the growing menace resulted out of this chronic disease, which is mostly resistant to conventional medicine, the medical fraternity is now in search of a new avenue. Homoeopathy often showed a positive response in Simple and Mucopurulent Chronic Bronchitis but it utterly lacked documentation. To have a proper documentation, the Central Council for Research In Homoeopathy started an open clinical trial on Simple and Mucopurulent Chronic Bronchitis at its seven centres including Regional Research Institute for Homoeopathy, Guwahati, on a set protocol . This is a case of 30 yrs. old woman of middle socio-economic status diagnosed as a case of simple chronic bronchitis. This case was enrolled and treated as per the protocol provided by the CCRH, New Delhi & outcome showed marked improvement in the clinical status of the patient. The comparative study of radiology & pulmonary function tests ( pre and post treatment ) further showed the Homoeopathic medicinal efficacy. This article shows the importance of record keeping in homoeopathy.